Genomic regions associated with milling quality and grain shape identified in a set of random introgression lines of rice (Oryza sativa L.) - Zheng, T.Q.; Xu, J.L.; Li, Z.K.; Zhai, H.Q.; Wan, J.M. (Wiley, 2007)
Rice milling quality is the final part of grain yield making it fit for eating and a complex trait that remains poorly understood genetically. Three components of rice milling quality, i.e. brown rice rate, milled rice rate and head rice rate and related rice grain shape traits were genetically dissected by the QTL mapping approach using a set of 231 random rice introgression lines and 160 SSR markers. A total of 10 genomic regions were found to be associated with rice grain shape and milling quality traits. Of these, one major QTL on chromosome 7 had large effects on rice grain shape and milling quality and was detected consistently in several related populations of rice, which offers an opportunity for marker‐aided improvement of rice milling quality and QTL cloning.